2022
DOI: 10.1126/sciadv.abn5803
|View full text |Cite
|
Sign up to set email alerts
|

Cortical-subcortical structural connections support transcranial magnetic stimulation engagement of the amygdala

Abstract: The amygdala processes valenced stimuli, influences emotion, and exhibits aberrant activity across anxiety disorders, depression, and PTSD. Interventions modulating amygdala activity hold promise as transdiagnostic psychiatric treatments. In 45 healthy participants, we investigated whether transcranial magnetic stimulation (TMS) elicits indirect changes in amygdala activity when applied to ventrolateral prefrontal cortex (vlPFC), a region important for emotion regulation. Harnessing in-scanner interleaved TMS/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 76 publications
4
30
0
Order By: Relevance
“…Across paradigms of both emotional and symptom provocation, OCD shows increased activation in the rostral ACC and other areas such as vmPFC, OFC, putamen and amygdala [47]. Together these findings are consistent with abnormalities in hyperactivity and functional connectivity in aversive affective processing identified in OCD [42,47,48], and abnormal processing within the corticostriatal loops [50][51][52][53][54]. OCD subjects have also shown impaired extinction learning, a process believed to involve a parallel inhibitory learning process [15].…”
Section: Ocd Controls: Task Validationsupporting
confidence: 57%
“…Across paradigms of both emotional and symptom provocation, OCD shows increased activation in the rostral ACC and other areas such as vmPFC, OFC, putamen and amygdala [47]. Together these findings are consistent with abnormalities in hyperactivity and functional connectivity in aversive affective processing identified in OCD [42,47,48], and abnormal processing within the corticostriatal loops [50][51][52][53][54]. OCD subjects have also shown impaired extinction learning, a process believed to involve a parallel inhibitory learning process [15].…”
Section: Ocd Controls: Task Validationsupporting
confidence: 57%
“…Beyond these local effects, the approach is particularly well-suited to study neural dynamics in large-scale brain networks: researchers can causally perturb neural function in one area and observe the propagation of signals throughout the brain. Consistent with our experimental findings, previous work that applied TMS during the resting state has found that stimulation to one node in a network can elicit increased fMRI signal in anatomically remote regions in the same network ( Bestmann et al, 2003b , 2004 , 2008a ; Denslow et al, 2005 ; Ruff et al, 2009 ; Bestmann and Feredoes, 2013 ; Hawco et al, 2018 ; Oathes et al, 2021 ; Sydnor et al, 2022 ). Although resting-state studies provide an important first step to characterize the local and distributed effects of TMS, combining concurrent TMS-fMRI with experimental tasks and behavioral measures is critical to studying cognitive function.…”
Section: Discussionsupporting
confidence: 92%
“…A FIR model can be used to verify whether any discovered activation follows the canonical HRF or whether it tracks with an expected signal dropout radiating from the location of the TMS coil at the time of discharge. Our results also provide causal evidence that TMS delivered to PFC activates both the region under the coil and anatomically connected regions in the dorsal striatum in line with previous subcortical-targeted TMS-fMRI studies ( Hermiller et al, 2020 ; Sydnor et al, 2022 ). Furthermore, we found causal evidence supporting the rostrocaudal hierarchy in PFC, characterized by asymmetrical projections toward more posterior sites ( Verstynen et al, 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…A previous study has found that rTMS can reach deep subcortical structures such as the amygdala through stimulation of cortical regions by cortico-subcortical structural connections [54]. Although the strongest stimulation effects remain at the scalp level, and rapidly attenuates as it crosses to brain tissue, the activations spread to other sites via axonal connections and the releasing of neurotransmitters, leading to deep structural and functional network changes [10,55].…”
Section: Discussionmentioning
confidence: 99%